2015
DOI: 10.1016/j.immuni.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Human Antibodies Fix Complement to Inhibit Plasmodium falciparum Invasion of Erythrocytes and Are Associated with Protection against Malaria

Abstract: SummaryAntibodies play major roles in immunity to malaria; however, a limited understanding of mechanisms mediating protection is a major barrier to vaccine development. We have demonstrated that acquired human anti-malarial antibodies promote complement deposition on the merozoite to mediate inhibition of erythrocyte invasion through C1q fixation and activation of the classical complement pathway. Antibody-mediated complement-dependent (Ab-C′) inhibition was the predominant invasion-inhibitory activity of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
338
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(359 citation statements)
references
References 46 publications
(77 reference statements)
19
338
2
Order By: Relevance
“…In agreement with preclinical studies, these data confirmed the vaccine-induced antibodies in humans were strain transcending, showing activity against all tested parasites. Notably, addition of human complement did not increase levels of GIA, as reported for some merozoite surface proteins (65). This is perhaps not surprising, given that antibodies only have a very short window of opportunity to bind RH5 following its release from the rhoptries, likely leading to time constraints on complement recruitment.…”
Section: Discussionsupporting
confidence: 56%
“…In agreement with preclinical studies, these data confirmed the vaccine-induced antibodies in humans were strain transcending, showing activity against all tested parasites. Notably, addition of human complement did not increase levels of GIA, as reported for some merozoite surface proteins (65). This is perhaps not surprising, given that antibodies only have a very short window of opportunity to bind RH5 following its release from the rhoptries, likely leading to time constraints on complement recruitment.…”
Section: Discussionsupporting
confidence: 56%
“…Hodder et al , 2001; Miura et al , 2009; Reiling et al , 2012; Schwartz et al , 2012). In a new study, however, Boyle et al (2015) demonstrated that acquired invasion‐inhibitory antibodies act through binding of C1q and activation of the classical complement pathway rather than by functionally inhibiting invasion. Without active complement, the majority of antibodies against merozoite surface proteins like MSP1 were not effective.…”
Section: Discussionmentioning
confidence: 99%
“…A more comprehensive investigation of the antibody response showed that high-miR responders had significantly increased IgG1, IgG3, and IgM anti-merozoite responses compared with low responders. These observations are important, as IgG1 and IgG3 are cytophilic antibody subclasses that function against merozoite antigens by fixing complement to the merozoite surface, inhibiting invasion (25) and enhancing opsonic phagocytosis (26). Moreover, cytophilic subclass antibodies (IgG1 and IgG3) against MSP1 and MSP2 have been associated with protection from malaria in longitudinal cohort studies in children (23,24,27).…”
Section: Discussionmentioning
confidence: 99%